2010
DOI: 10.1208/s12249-010-9454-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Safety, Pharmacokinetics, and Pharmacodynamics of Liposomes Containing Brucea javanica Oil

Abstract: Abstract. Brucea javanica oil-loaded liposomes (BJOL) were prepared through thin film hydration method and characterized by transmission electron microscope, dynamic light scattering, and differential scanning calorimetry. Acute toxicity of B. javanica oil (BJO) in liposomes was assessed by determining the number of deaths of Kunming mice over intravenous treatment for 2 weeks. The pharmacokinetic behavior of the main active component (oleic acid) was studied in SD rats. The pharmacodynamics of BJOL was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Brucea javanica oil extracted with petroleum ether from the fuits of B. javanica, is a complex mixture of fatty acids, which were reported to be cytotoxic active constituents [13]. The cytotoxic activity of petroleum ether fractions can be explained partly, by the high concentration of fatty acids and minor components such as sterides, pregnanones [18] and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucea javanica oil extracted with petroleum ether from the fuits of B. javanica, is a complex mixture of fatty acids, which were reported to be cytotoxic active constituents [13]. The cytotoxic activity of petroleum ether fractions can be explained partly, by the high concentration of fatty acids and minor components such as sterides, pregnanones [18] and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on the constituents of the ethyl acetate and n-butanol extracts of B. javanica. Brucea javanica oil (BJO) is a petroleum ether extract is mainly composed of fatty acids and fatty acid derivatives, which were extracted with petroleum ether from the fruits of B. javanica [13]. It has been used as anti-tumor agent to therapy hepatic, esophageal, rectal, pulmonic, renal, and prostatic carcinomas clinically [14].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the freeze-dried product was quite good and when compared with injection of the oil emulsion, the liposomes containing Brucea javanica oil had stronger antitumor activity with less toxicity. 38 Further, some researchers have reported the effect of these liposomes on human hepatoma cells, indicating that they inhibited proliferation of HepG2 cells and induced apoptosis, which suggests good potential for liposomal Brucea javanica in antineoplastic therapy. 39 …”
Section: Nanoparticulate Drug Delivery Systemsmentioning
confidence: 99%
“…2 Oleic and linoleic acids in BJO are the main active ingredients for the antitumor activity (the total acid content in refined BJO is .95%), 3 and conjugated fatty acid can be metabolized to free fatty acids -oleic acid, producing effect in the body. 4,5 Many studies have shown that BJO has a variety of pharmacological activities, including anti-HIV (human immunodeficiency virus), antimalarial, antituberculosis, cytotoxic, and antitumor activities.…”
Section: Liu Et Almentioning
confidence: 99%
“…Related literatures have reported that the content of free fatty acid in fasting rats increases significantly (but fasting has different effect on free fatty acid in each rat), for example, the plasma concentration of oleic acid in rats was ~100 μg⋅mL -1 in the morning, 43,44 which is consistent with the results obtained in this experiment. Because there was a large amount of oleic acid in the fasting rats affecting the determination of oleic acid from the external source, we used the difference in value of oleic acid between the administration group and the blank group as the absorption of exogenous oleic acid 3 (as shown in Figure 6) and then calculated the related pharmacokinetic parameters (as listed in Table 2). Results indicated that compared with the BJO-E, AUC 0→∞ of BJO-CN significantly increased and that the relative bioavailability of BJO-CN to BJO-E was 1.6 times.…”
Section: Pharmacokinetic Studies In Ratsmentioning
confidence: 99%